Oxidation behaviour at 1100°C in air of 25 wt-% Cr-containing cobalt-based alloys containing high quantities of hafnium carbides. (1st October 2016) - Berthod, P.; Conrath, E.
Abstract : Hafnium, usually added to improve the high temperature oxidation resistance of alloys, allowed obtaining HfC carbides which are very efficient for the creep-resistance. For that Hf must be added in particularly high quantities which may possibly influence the oxidation behaviour. Three HfC-strengthened cast cobalt alloys were studied all along thermogravimetry tests at 1100°C. They were compared to similar but Hf-free ternary alloys. The mass variation were plotted according to { m  ×  dm / dt  =  f (– m )} to specify all kinetic oxidation constants, and versus temperature to study the oxidation beginning during heating and the scale spallation during cooling. The presence of many HfC carbides obviously influences the high temperature oxidation: mass gain occurring sooner during heating, faster isothermal mass gains but better behaviour in oxide scale spallation during cooling. This deterioration of oxidation behaviour must be corrected to hope benefiting from the high creep-resistance brought by this new type of strengthening. GRAPHICAL ABSTRACT: